O percurso de desenvolvimento profissional de uma professora estagiária de Educação Física - Inês Rafaela da Costa Ferreira (2023)
This report was drawn up as part of the Professional school placement within the Master's Degree in Teaching Physical Education in Primary and Secondary Schools at the Faculty of Sport of the University of Porto. This document is called a professional school placement and reports on what happened along the way by the school placement. This course is characterized as a supervised teaching practice that offers the preservice teacher immense first-person experiences of their role as a teacher. Supervision was carried out by specialised professionals in the field, a cooperating teacher at the school daily and a supervising teacher assigned by the faculty. The internship took place in a primary and secondary school. The first period was discovery and knowledge, discovering the school environment, getting to know the people, the context and the pupils. It was also characterised by fear and uncertainty about what lay ahead. This first period was crucial for planning and defining objectives, and it was also the most labour-intensive since we had to build everything from scratch. Full of unpredictability and challenges, the second period was the most challenging. The good atmosphere among the internship team was one reason I could finish this course. The third period passed in the blink of an eye, it was the most rewarding and challenging period as I realized I was ending this experience. It was also the period with the most activities with the students, especially the older ones, which allowed me to enjoy the good part of being a teacher, sharing moments with the students. In the end, I closed another cycle in my life to open an even bigger one. After learning and adapting, I leave as a richer and more capable person.